A systematic review of modalities in computer-based interventions (CBIs) for language comprehension and decoding skills of children with autism spectrum disorder - Khowaja, Kamran; Salim, Siti Salwah; Zavareh, Adeleh Asemi; Ghulamani, Sumbul; Shah, Asadullah (Springer New York LLC, 2019)
This paper presents a systematic review of the literature on the modalities used in computer-based interventions (CBIs)and the impact of using these interventions in the learning, generalization, and maintenance of language comprehension and decoding skill for children with autism spectrum disorder (ASI), ending with appraisal of the certainty of evidence. Despite the importance of both skills in the reading comprehension and overall learning a limited number of studies have been found. These include seven studies in language comprehension and seven studies on decoding. The shortlisted studies were analysed and a very limited number of modalities were found to have been used; text, graphics, audio, video, and mouse movements are used in all the studies and are termed basic modalities. Statistical analysis was also conducted on three parameters: (1) outcome of the study; (2) generalization; and (3) maintenence. The analysis showed that CBIs were effective in facilitating these children's learning; there was a significant improvement in the performance of children from the baseline to during and the post-intervention period. The analysis of generalization has revealed positive results are also noted from the analysis of maintenance, which indicate that the children retained information following the withdrawal of intervention. The combination of teachers's instruction and CBI has provided better results than using either of them separately. This study has discovered 23 potential modalities and 2 potential CBIs including serious games and virtual learning environments that can be explored for language comprehension and decoding skills.